Branding as a part of brand management - Bondarenko, K. S. (ТДАТУ, 2020)
It is not uncommon for company owners to ask marketing organizations to draw some logo, thinking that this is a full-fledged brand building. Not understanding the difference between definitions such as “branding” and “corporate identity”, a manager wastes his time and loses money
Keywords: branding; full-fledged brand; brand; design